Net charge and oxygen affinity of human hemoglobin are independent of hemoglobin concentration (The Rockefeller University Press, 1978)
The dependence of net charge and oxygen affinity of human hemoglobin upon hemoglobin concentration was reinvestigated. In contrast to earlier reports from various laboratories, both functional properties of hemoglobin were found to be independent of hemoglobin concentration. Two findings indicate a concentration-independent net charge of carbonmonoxy hemoglobin at pH 6.6: (A) The pH value of a given carbonmonoty hemoglobin solution remains constant at 6.6 when the hemoglobin concentration is raised from 10 to 40 g/dl, indicating that there is no change in protonation of titratable groups of hemoglobin: (b) the net charge of carbonmonoxy hemoglobin as estimated from the Donnan distribution of 22Na+ shows no dependence on hemoglobin concentration in this concentration range. The oxygen affinity of human hemoglobin was determined from measurements of oxygen concentrations in equilibrated samples using a Lex-O2-Con apparatus (Lexington Instruments, Waltham, Mass.). P50 averaged 11.4 mm Hg at 37 degrees C, pH = 7.2, and ionic strength approximately 0.15. Neither P50 nor Hill's n showed any variation with hemoglobin concentrations increasing from 10 to 40 g/dl.